‘God Gave us Legs to Walk!’ - Marizanne Grundlingh (The Thinker)
Domestic work is a major source of income for many Black African women in South Africa. The experience of domestic workers is mainly shaped along racial and class lines – this is a result of the remnants of the legacy of apartheid, where many Coloured and African women were dependent on employment in the domestic work sphere. This article considers the experiences of a group of Coloured female domestic workers in a coastal town in South Africa. Drawing on ten qualitative interviews, I show how their experiences are framed around issues of mobility – this includes moving to work and moving at work and the consequences of immobility in the world of work. Most research that deals with issues of mobility in domestic work focuses on migration patterns. This novel approach to understanding the notion of mobility for domestic workers contributes to the existing literature on domestic work in South Africa but extends the conceptualisation of movement beyond migration patterns. The article also makes a much-needed contribution to understanding the experience of domestic work in rural settings in South Africa. This is done by exploring the coping strategies that the participants employ to support themselves and their families. Networks and family ties form an essential component of the financial and emotional survival of this group of women. The role of social capital is also investigated as it plays an important role in forging trust and reciprocity among participants of this study.